A literature review on knowledge, awareness and attitude related to first aid among university students - Jamaludin, Thandar Soe Sumaiyah; Zakaria, Muhammad Allif; Saidi, Sanisah; Mei Chan, Chong (Scholars Academic and Scientific Publisher, 2018)
Having knowledge and awareness related to first aid in each individual person is important in terms of helping people in emergency situation since injuries are one of the leading causes of morbidity and mortality worldwide. On the other hand, first aid is the treatment for the purpose of preserving life and minimizing the consequences of injury and illness until getting help from a medical practitioner or nurse. Furthermore, some studies have found that individual person who equipped with adequate first aid knowledge had a positive impact on morbidity and mortality worldwide. Therefore, this literature review was aimed to evaluate the knowledge, awareness, and attitude related to first aid among university students. The finding of this literature showed that the level of knowledge, awareness, and attitude related to first aid among university students are varied and inadequate although they knew this course is important.